A longitudinal investigation of the glass-ceiling in nursing. Issue 2 (29th April 2019) - Woolnough, Helen; Fielden, Sandra; Crozier, Sarah; Hunt, Carianne
Abstract : Purpose: The purpose of this paper is to present a longitudinal, qualitative study exploring changes in the attributional constructions of sense-making in the perceptions and lived experiences of the glass-ceiling among a cohort of female mental health nurses in the National Health Service who participated in a 12-month multi-faceted career and leadership development pilot programme compared to a matched control group. Design/methodology/approach: The authors interviewed 27 female mental health nurses in the UK who participated in a multi-faceted development programme specifically designed to support female nurses secure career advancement and 27 members of a matched control group who did not experience the programme. Participants engaged in semi-structured telephone interviews at three separate time points (six months apart) over a 12-month period. Findings: Programme participants differed in their attributional constructions of sense-making in relation to the glass-ceiling over time compared to the matched control group, e.g., triggering understandings and awakenings and re-evaluating the glass-ceiling above when promoted. Findings are used to theorise about the glass-ceiling as a concept that shifts and changes over time as a function of experience. Practical implications: Practical implications include important organisational outcomes in relation to fostering the career advancement and retention of talented female leaders at all career stages. Originality/value: The authors present the first known longitudinal, qualitative study to explore changes in attributional constructions of sense-making in perceptions and experiences of the glass-ceiling among female nurses over time compared to a matched control group.